2001
DOI: 10.1097/00000421-200110000-00007
|View full text |Cite
|
Sign up to set email alerts
|

Expression of Inflammatory Modulator COX-2 in Pancreatic Ductal Adenocarcinoma and Its Relationship to Pathologic and Clinical Parameters

Abstract: Despite the exceedingly poor prognosis of pancreatic cancer, it is often histologically well to moderately differentiated. The apparent resistance to conventional therapeutic modalities is poorly understood and may be related to the molecules involved in its progression or its propensity for perineurial invasion. Cyclooxygenase-2 (COX-2) is an inducible enzyme homologous to COX-1 that is responsible for production of prostaglandins at sites of inflammation. It is activated by a variety of growth factors and tu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

6
58
2
1

Year Published

2004
2004
2019
2019

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 78 publications
(67 citation statements)
references
References 20 publications
6
58
2
1
Order By: Relevance
“…[3][4][5] Cox-2 overexpression leads to an enhanced production of prostaglandin E2 (PGE2), which is involved in tumor progression as well as in tumor evasion of immunosurveillance. 6 The release of PGE2 by cancer cells induces and recruits regulatory T cells to the tumor site and suppresses immune responses of CD8 C ab T cells and natural killer (NK) cells as well as maturation of dendritic cells.…”
Section: Introductionmentioning
confidence: 99%
“…[3][4][5] Cox-2 overexpression leads to an enhanced production of prostaglandin E2 (PGE2), which is involved in tumor progression as well as in tumor evasion of immunosurveillance. 6 The release of PGE2 by cancer cells induces and recruits regulatory T cells to the tumor site and suppresses immune responses of CD8 C ab T cells and natural killer (NK) cells as well as maturation of dendritic cells.…”
Section: Introductionmentioning
confidence: 99%
“…[7][8][9][10][11] Increased expression of COX-2 has also been observed in pancreatic cancer, irrespective of histological type and grade, but the mechanisms that control the constitutive and induced expression of COX-2 in human pancreatic carcinoma cells are not completely understood. [12][13][14][15][16][17] The transcriptional activation of COX-2 is mediated by the binding of transcription factors to regulatory elements in the COX-2 promoters, such as nuclear factor κB (NF-κB), CCAAT/enhancerbinding protein (C/EBP), cyclic AMP response element-binding protein (CREB) and nuclear factor-activated T-cell/AP-1, which are involved in COX-2 induction in response to a variety of stimuli in different species and cell types. [18][19][20][21][22][23] For example, the C/EBP family of transcription factors plays an important role in COX-2 induction by lipopolysaccharide and phorbol ester in human vascular endothelial cells, 18 by tumor necrosis factor-α in murine MC3T3-E1 osteoblastic cells, 19 and in mouse skin carcinoma cells.…”
Section: Introductionmentioning
confidence: 99%
“…12 Mounting evidence derived from clinically proven biopsy samples showed that COX-2 is upregulated in human pancreatic tumor tissues as compared with normal adjacent pancreatic tissues. [13][14][15] Moreover, COX-2 inhibitors inhibit cell growth with greater efficacy in cell lines with stronger COX-2 expression compared with weakly COX-2 expressing PC cell lines. 14,16 Further studies have shown that genetic deletion of COX-2 abrogates tumorigenesis as well as intestinal polyposis in mouse model of familial adenomatous polyposis APC D716 compared with wild type animal.…”
mentioning
confidence: 99%
“…17,18 Studies from our laboratory have also shown over expression of COX-2 in pancreatic ductal adenocarcinoma, which was associated with increased perineural invasion. 15 Despite numerous advances in our understanding of the pathophysiology and molecular biology of PC, currently available standard therapeutic approach for PC show limited benefit in improving the survival of patients diagnosed with this deadly disease. NSAIDS are well studied class of chemopreventive agents and have been shown to act through both COX dependent 19,20 and independent pathways.…”
mentioning
confidence: 99%